SIMATREN-DI: Pengembangan dan Implementasi Manajemen Rapat dan Peran Pengguna Pada Sistem Informasi Manajemen Sumber Daya Manusia Pada Pesantren - Audyningrum, Nurul Qofifah; Mandasari, Rizza Indah Mega (eProceedings of Applied Science, 2025)
Abstract—The manual human resource (HR) management at Husnul Khotimah Islamic Boarding School has led to inefficiencies in tracking employee attendance, particularly for meetings. Furthermore, the previous SIMATREN web system lacked user role management, which hindered access based on individual employee responsibilities. To address these issues, SIMATREN-DI was developed as a web-based application integrating Human Resource Information System (HRIS) technology. This system introduces features for meeting management and user role administration, allowing for more structured data and attendance recording. It also implements user role settings and self-service access to ensure that employees can only access functions corresponding to their authority. The project was developed using the prototyping model to ensure its alignment with user requirements. Based on testing with the System Usability Scale (SUS), the application achieved a final score of 79.58, indicating good usability and positive reception among the users. Keywords— Human Resource Management, HRIS, Meeting Management, User Roles, Information System, Islamic Boarding School